Measuring Undernutrition Through Z-Scores and Composite Index of Anthropometric Failure (CIAF): A Study Among Slum Children in Ahmedabad City, Gujarat - Solanki, Rajanikant; Patel, Tushar; Shah, Hasmukh; Singh, Uday Shankar (National Journal of Community Medicine, 2014)
Background: Undernutrition continues to be underlying cause of morbidity and premature mortality among children in India. The primary goal of our study was to investigate the prevalence of child undernutrition and applying Svedberg theory to construct Composite Index of Anthropometric Failure (CIAF) Methods: We used cross-sectional anthropometric data for 372 child-mother pairs which were selected using two stage sampling. Anthropometric measurements was used to determine if children were low weight for age (underweight), low height for age (stunting) and low weight for height (wasting) based on WHO child growth standards and later used for construction of CIAF. Epi Info 7 and Anthro software used to calculate Z-scores and statistical analysis. Results: Based on CIAF, the prevalence of undernutrition was 60.5%. Of the children included in the study, 42.7% found to be underweight, 15% being found to have wasting and 50% showing sign of stunting. Using underweight as the only criterion for identifying undernourished children may underestimate the true prevalence by as much as 17.5%. Conclusion: Undernutrition still an important public health problem in this region. Use of WHO Z-score system recommended for identifying all aspects of undernutrition.